Bioinformatics Analysis Identifies CPZ as a Tumor Immunology Biomarker for Gastric Cancer - Gu, Yuan; Gao, Ying; Tang, Xiaodan; Xia, Huizhong; Shi, Kunhe (Current Bioinformatics, 2021)
Background: Gastric cancer (GC) is one of the most common malignancies worldwide. However, the biomarkers for the prognosis and diagnosis of Gastric cancer are still need. Objective: The present study aimed to evaluate whether CPZ could be a potential biomarker for GC. Methods: Kaplan-Meier plotter (http://kmplot.com/analysis/) was used to determine the correlation between CPZ expression and overall survival (OS) and disease-free survival (DFS) time in GC. We analyzed CPZ expression in different types of cancer and the correlation of CPZ expression with the abundance of immune infiltrates, including B cells, CD4+ T cells, CD8+ T cells, neutrophils, macrophages, and dendritic cells, via gene modules using TIMER Database. Results: The present study identified that CPZ was overexpressed in multiple types of human cancer, including gastric cancer. We found that overexpression of CPZ correlates to the poor prognosis of patients with STAD. Furthermore, our analyses show that immune infiltration levels and diverse immune marker sets are correlated with levels of CPZ expression in STAD. Bioinformatics analysis revealed that CPZ was involved in regulating multiple pathways, including PI3K-Akt signaling pathway, cGMP-PKG signaling pathway, Rap1 signaling pathway, TGF-beta signaling pathway, regulation of cell adhesion, extracellular matrix organization, collagen fibril organization, and collagen catabolic process. Conclusion: This study, for the first time, provides useful information to understand the potential roles of CPZ in tumor immunology and validate it to be a potential biomarker for GC.
Keywords: cell